(untitled) (Raparin Journal of Humanities (RJH), 2025)
In this research, the researcher has worked on investigating about Kurdish design clothes and its reflections especially in contemporary art in Kurdistan Region of Iraq. This research presents the basic concept of authenticity in Kurdish fashion design and its characteristics. This research contains four chapters. The first one of the research is devoted to the general framework of the research, which is containing the Research problem and the main questions, such as presenting the issue of authenticity and arguing the reasons behind the unique form of Kurdish clothing design and the differences with neighborhood countries, as well as presenting a central question about the factors of reflecting Kurdish clothing design within contemporary painting in Kurdistan Region. The first section also includes terms and glossary definition, according to the definition of words in the linguistic context in addition to the concepts definition of the term, in the field of its usage and to be matching the procedures of the recent research. While the second chapter of this research is devoted to the theoretical framework of the research, which consists of two topics, the first topic is entitled (The Basic Elements of Design), while the second topic is entitled (A brief study about the roots of Kurdish Clothing).